Life-cycle management of deteriorating civil infrastructure considering resilience to lifetime hazards: A general approach based on renewal-reward processes - Yang, David Y.; Frangopol, Dan M. (Reliability engineering & system safety, 2019)
•An approach is proposed for structures under progressive and sudden deterioration.•The proposed approach is based on the renewal theory of renewal-reward processes.•The lifetime resilience losses are proposed to consider resilience to lifetime hazards.•Multi-objective optimization is used for life-cycle management.•The optimization considers intervention costs, failure risks and resilience losses. Civil infrastructure during its service life is subject to progressive deterioration due to aggressive environments and sudden deterioration due to natural and/or manmade hazards. This paper presents a general approach to perform life-cycle management considering both types of deterioration. As an important aspect of life-cycle asset management under hazards, the present study introduces a novel concept, referred to as lifetime resilience. The lifetime resilience of a deteriorating structure is characterized by its cumulative losses to lifetime hazards. By modeling lifetime hazards and life-cycle performance as renewal-reward processes, the proposed approach resorts to the renewal theory to formulate analytical expressions of expected values of lifetime intervention costs, lifetime failure risks, and lifetime resilience losses. Owing to the efficiency in evaluating these expressions, a generic life-cycle management framework is proposed using multi-objective optimization. This proposed framework is applicable to a wide range of civil infrastructure systems under various types of hazards. The proposed approach is illustrated by using a numerical example.